Degradation of Tetracycline by Composite Catalyst Derived from Food Waste and Goethite - Huynh Quang Sang; Huynh Nguyen Cao Thong; Nguyen Thao Ha; Vo Thi Yen Linh; Nguyen Duy Dat; Tran Thi Kim Anh (Journal of Technical Education Science, 2024)
Current studies on the removal of emerging contaminants (such as pharmaceuticals, personal care products, and their metabolites) from environmental matrices have received a lot of interest due to their adverse impacts on human health and ecology. Among these emerging contaminants, Tetracycline hydrochloride (TCH) - has become a common antibiotic prominent found in hospital and municipal wastewater. The present research develops soybean curd biochar loading goethite (SBCG) and soybean curd activated carbon loading goethite (SACG), a magnetic material made from soybean curd residue and Fe precursor (α-FeOOH), for advanced oxidation processes (AOPs) of TCH in aqueous solutions. Soybean curd biochar loading goethite and soybean curd activated carbon loading goethite demonstrated decomposition performances of 82.8% and 95.3% for the oxidizing agent H2O2 at pH 2, and 87.2% and 94.8% for the oxidizing agent K2S2O8 at pH 7, respectively. Furthermore, the oxidant utilized in the reaction was more H2O2 than K2S2O8. In which the initial concentration was 70 mM H2O2 and 20 mM K2S2O8, the residual concentration after the reaction was 19 - 22 mM H2O2 and 6.5 – 9.35 mM K2S2O8 for SACG and SBCG. The consumption of H2O2 and K2S2O8 per unit treatment agent for SACG material with an initial TCH concentration of 300 mg/L was 75.5 and 20mmol oxidant/mmol TCH, respectively. This demonstrates that combining K2S2O8 with SACG produces the most beneficial outcomes, such as saving time, chemicals, and the amount of post-treated water with a neutral pH value.